2008
DOI: 10.1088/1748-6041/3/4/045001
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking methods of electrospun fibrinogen scaffolds for tissue engineering applications

Abstract: The purpose of this study was to enhance the mechanical properties and slow the degradation of an electrospun fibrinogen scaffold, while maintaining the scaffold's high level of bioactivity. Three different cross-linkers were used to achieve this goal: glutaraldehyde vapour, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) in ethanol and genipin in ethanol. Scaffolds with a fibrinogen concentration of 120 mg ml(-1) were electrospun and cross-linked with one of the aforementioned cross-linkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 39 publications
(60 reference statements)
0
86
0
Order By: Relevance
“…To prepare genipin cross-linked L-PRF, rinse membranes with PBS and soak in 4 ml of 1% genipin solution (in 70% ethanol) for 48 hr. Rinse with PBS prior to experiments to remove excess genipin 15,16 . 2.…”
Section: Genipin Crosslinking Of L-prf Trypsin Susceptibility and Nimentioning
confidence: 99%
“…To prepare genipin cross-linked L-PRF, rinse membranes with PBS and soak in 4 ml of 1% genipin solution (in 70% ethanol) for 48 hr. Rinse with PBS prior to experiments to remove excess genipin 15,16 . 2.…”
Section: Genipin Crosslinking Of L-prf Trypsin Susceptibility and Nimentioning
confidence: 99%
“…However, prior publications with electrospun Fg matrix lacked mechanical stability to serve as tissue engineering scaffolds without crosslinking, as the Fg scaffolds completely dissociated in 1-2 weeks of culture, a problem consistently observed with electrospun collagen scaffolds [38]. While the mechanical properties of electrospun Fg may be augmented by chemical crosslinking, we have previously reported that chemical crosslinking inhibits cell growth and differentiation [37]. Blending Fg with a synthetic polymer, such as PDO, improves scaffold stability in media [33,37].…”
Section: Discussionmentioning
confidence: 97%
“…Solutions of lyophilized bovine Fg (Fraction 1, Type 1-S from bovine plasma, Sigma Aldrich) were made with a 10% (by volume) 10X minimal essential medium (MEM, Sigma Aldrich) and 90% 1,1,1,3,3,3 hexafluoro-2-propanol (HFP; TCI America, Portland, OR) at concentrations of 100 mg/mL (ratio determined to make biomimetic fiber diameters as described in our prior work [37]), and allowed to dissolve overnight with shaking. Solutions of PDO (Ethicon, Somerville, NJ) were made at 100 mg/ml concentrations, dissolved in HFP overnight with shaking at room temperature (RT).…”
Section: Electrospinning Fg Pdo and Fg:pdomentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-linking of fibrinogen scaffolds has also been used to increase their mechanical strength and slow their rate of degradation. The authors of this review [106] have used both EDC and genipin to successfully alter the properties of electrospun fibrinogen, with cross-linked scaffolds remaining mechanically viable after 14 days in culture compared to complete loss of mechanical integrity after 7 days for non-cross-linked scaffolds. The degree to which these scaffolds were cross-linked decreased the rate of scaffold remodeling, with little new collagen matrix visible in Masson's trichrome histological stains after 21 days in culture with FBs.…”
Section: Electrospinning Fibrinogenmentioning
confidence: 99%